2015
DOI: 10.1016/j.plefa.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid supplementation in lactating women increases breast milk and plasma docosahexaenoic acid concentrations and alters infant omega 6:3 fatty acid ratio

Abstract: This study investigated the effects of docosahexaenoic acid (DHA) supplementation on the fatty acid composition of breast milk and plasma concentrations in lactating women and their infants. Eighty-nine lactating women 4-6 weeks post-partum received placebo, 200 mg or 400 mg DHA for 6 weeks with usual diets. Breast milk fatty acids and maternal plasma fatty acids were measured at the beginning and end of the study and infant plasma at the end of the study. Breast milk and maternal plasma DHA were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 43 publications
5
51
0
2
Order By: Relevance
“…This may have provided added protection to the pups, since the postnatal hyperoxia extended to PND14 and probably also modulated lung repair until PND21 when the mice are usually weaned. This effect has also been shown in human studies, where breastfeeding mothers receiving DHA supplementation had higher DHA concentration in their breast milk (7,40). This model would have clinical relevance for preterm neonates, since they may receive their mother's own milk, donor human milk, or preterm formula in the neonatal intensive care unit.…”
mentioning
confidence: 55%
“…This may have provided added protection to the pups, since the postnatal hyperoxia extended to PND14 and probably also modulated lung repair until PND21 when the mice are usually weaned. This effect has also been shown in human studies, where breastfeeding mothers receiving DHA supplementation had higher DHA concentration in their breast milk (7,40). This model would have clinical relevance for preterm neonates, since they may receive their mother's own milk, donor human milk, or preterm formula in the neonatal intensive care unit.…”
mentioning
confidence: 55%
“…Weil entzündungsauflösende Lipidmediatoren bzw. n-3-PUFA sowohl in der Plazenta und im Nabelschnurblut (Keelan et al 2015) als auch in der Muttermilch (Sherry et al 2015) nachweisbar sind, und Resolvine und Protektine die Atemwegsinflammation, muköse Metaplasie und Hyperreaktivität der Bronchien reduzieren sowie Schutz vor respiratorischen Infektionen bieten können, erweist sich diese Studie als klinische Bestätigung des bisherigen hauptsächlich experimentellen Wissens über die oben beschriebenen Lipidmediatoren.…”
Section: Omega-3-substitution In Der Schwangerschaftunclassified
“…Although DHA can be synthesized from its ω3 precursor (ALA) 16 , studies have shown that DHA from the maternal diet is more efficient in source of neural tissue DHA than in an equivalent amount precursor of ALA 17,18 Increasing attention over the last 20 years upon DHA in pregnancy and lactation for its role in brain development, as it accounts for over 10% of brain fatty acids is essential for infant brain development [25][26][27][28] . Infant brain doubles in weight, and the large brain to body weight ratio for infants (0.1) compared with adults (0.02) may put the infant at higher risk of deficiency in brain nutrients and energy 29,30 .…”
Section: International Journal Of Pharma Research and Health Sciencesmentioning
confidence: 99%
“…Infant brain doubles in weight, and the large brain to body weight ratio for infants (0.1) compared with adults (0.02) may put the infant at higher risk of deficiency in brain nutrients and energy 29,30 . To anticipate this condition, mother diets in DHA intake is recommended in corresponding to the formation of neural synapses which are rich in DHA, neurite outgrowth, dendritic complexity and neurotransmitter metabolism are also highly reliant on DHA 17,31,32 . This review will give wide aspects on role and progress of DHA dietary supply in brain development, especially in pre-conception, maternal and early childhood which is known as golden age period.…”
Section: International Journal Of Pharma Research and Health Sciencesmentioning
confidence: 99%